Zchain4u based on blockchain technology - Abdol Rahman, Nurul Nadia (2018)
The growth of technology nowadays become a higher demand due to the fact of the era as from a manual system to an automatic machine. A lot of other changes affect in our world comes from a technology, mostly it comes to the digital communication also digital transmission. Digital transmission always is a platform for a hacker to hack another user, especially when the transmission is involved with financial. This project proposes a higher secure of digital transmission platform. This transmission is involved peer-to-peer network and decentralized consensus technique which to make all nodes using the transmission without a third party or dedicated server, to increased the anonymous of the user. The methodology used in this project is Merkle tree technology. Moreover, the platform is committed to cryptography technique, such as SHA256 and PKI. This technology is been proved to increase the integrity of the transmission and increased the trust of the sender and receiver of Zwallet user. A Zchain4u project has been concluding to be higher secure chain product to transmit Zcoin transactions.